Enhancing Inventory Control Through Barcode-Based Warehouse Management System: A Qualitative Analysis: Meningkatkan Pengendalian Inventori Melalui Sistem Manajemen Gudang Berbasis Kode Batang: Analisis Kualitatif - Nisa, Shofiyatun; Rahmawati, Imelda Dian (Indonesian Journal of Innovation Studies, 2023)
This research aims to investigate the implementation of a Barcode-Based Warehouse Management System (WMS) and its impact on Finish Good Inventory Control, employing qualitative techniques. The study identifies challenges associated with the manual information system in a corporate setting, leading to inventory discrepancies and inefficiencies. The findings demonstrate that the adoption of the new WMS enhances stock visibility, aids in resource allocation, and improves inventory accuracy, particularly in monitoring fast-moving and slow-moving items. This research underscores the significance of WMS for optimizing inventory management and its broader implications for operational efficiency and cost-effectiveness. Highlights: Efficient Inventory Tracking: The study emphasizes the role of the Warehouse Management System in enhancing real-time inventory tracking, reducing errors, and improving stock visibility. Cost-Effective Operations: Implementation of the Barcode-Based WMS offers cost-saving opportunities through efficient resource allocation and streamlined inventory management. Strategic Decision Support: The research highlights how accurate inventory data enables informed decisions regarding resource allocation, restocking strategies, and overall operational planning. Keywords: Warehouse Management System, Barcode-Based Inventory Control, Qualitative Analysis, Inventory Accuracy, Operational Efficiency